DESAIN SISTEM INFORMASI PENGGAJIAN UMKM BANDA ACEH (STUDI KASUS PADA USAHA MANUFAKTUR) - Evayani, Evayani; Kamil, Fauzan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
Payroll is one of the elements in the financial statements, which appears in the statement of financial position and income statement. Wrong and untimely salary management can affect the company's performance. One of the errors in salary management is caused by the implementation of a manual system, which allows for various problems in payment. This study aims to design a payroll information system that will help companies, especially SMEs, in managing salaries. This design process starts from recording to presenting the report. The system designed in this study uses the PHP programming language, and MySql as a server. This research uses a case study method, data collection in research through interviews, observations, and literature studies conducted directly at the company. This research produces an application system that makes it easier for companies to manage salaries in the future.